Piezoelectric Active Humidity Sensors Based on Lead-Free NaNbO3 Piezoelectric Nanofibers - Li Gu; Di Zhou; Jun Cheng Cao (Sensors, 2016)
The development of micro-/nano-scaled energy harvesters and the self-powered sensor system has attracted great attention due to the miniaturization and integration of the micro-device. In this work, lead-free NaNbO3 piezoelectric nanofibers with a monoclinic perovskite structure were synthesized by the far-field electrospinning method. The flexible active humidity sensors were fabricated by transferring the nanofibers from silicon to a soft polymer substrate. The sensors exhibited outstanding piezoelectric energy-harvesting performance with output voltage up to 2 V during the vibration process. The output voltage generated by the NaNbO3 sensors exhibited a negative correlation with the environmental humidity varying from 5% to 80%, where the peak-to-peak value of the output voltage generated by the sensors decreased from 0.40 to 0.07 V. The sensor also exhibited a short response time, good selectively against ethanol steam, and great temperature stability. The piezoelectric active humidity sensing property could be attributed to the increased leakage current in the NaNbO3 nanofibers, which was generated due to proton hopping among the H3O+ groups in the absorbed H2O layers under the driving force of the piezoelectric potential.